2015
DOI: 10.1038/cgt.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an apoptotic strain of Newcastle disease virus isolated from an outbreak in India

Abstract: Newcastle disease (ND) is a highly contagious disease of poultry. The ND virus (NDV) encodes an error-prone RNA-dependent RNA polymerase which can cause high mutation rate leading to the emergence of its new antigenic variants. Antigenic difference of NDV strains may result in massive outbreak in vaccinated and unvaccinated poultry flocks around the globe. Apart from its pathogenic potential NDV has been explored as an oncolytic agent for a broad range of human cancers. In the present study, we isolated a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Presence of virulent cleavage is reported to be one of the predisposing factors for NDV oncolysis 55 . The NDV related cell viability studies in oral cells were dose and time-dependent similar to earlier reported studies 56 . Furthermore, the apoptosis rate analyzed by Annexin V and PI staining 72 hr post-infection showed 39% Annexin V positive compared to control suggesting the cause of death might be apoptosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Presence of virulent cleavage is reported to be one of the predisposing factors for NDV oncolysis 55 . The NDV related cell viability studies in oral cells were dose and time-dependent similar to earlier reported studies 56 . Furthermore, the apoptosis rate analyzed by Annexin V and PI staining 72 hr post-infection showed 39% Annexin V positive compared to control suggesting the cause of death might be apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…After attachment, the cells were treated with different multiplicity of infections (MOI) by NDV (0.1, 0.01, and 0.001). The spectrophotometer readings were taken at regular intervals following the standard protocol 56 . Staurosporine (STS) at a concentration of 40 nM was used as a positive control in all the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NDV has gained significant attention in recent years not only because of its pathogenic nature for avian species but also because of its use as a vaccine vector and an oncolytic agent . In recent years, many new strains of NDV have been isolated and characterized . The analysis of complete genome sequence of newly isolated strains of NDV gives a comprehensive insight regarding the sequence variation among its different pathotypes.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the role of Tex13b in germ cells growth we did MTT assay for GTKO31 cells in compare with GC1 cells. The MTT assay was done every 24 hours according to protocol described in the previous study (Kumar & Kumar, 2015). Briefly, 500 cells were seeded for each GC1 and GTKO31 cells per well (12 wells each) of 96 well plate in DMEM growth media in 6 different plates and media was changed every 48 hrs.…”
Section: Proliferation Assaymentioning
confidence: 99%